Global spectrum of USH2A mutation in inherited retinal dystrophies: Prompt message for development of base editing therapy - Su, Bing-Nan; Shen, Ren-Juan; Liu, Zhuo-Lin; Li, Yang; Jin, Zi-Bing (Frontiers in Aging Neuroscience, 2022)
Purpose: Mutation in the USH2A gene is the most common cause of inherited retinal dystrophy (IRD), including non-syndromic retinitis pigmentosa (RP) and Usher syndrome II (USH2). Gene editing and therapy targeting USH2A, especially the hotspot region, would benefit a large proportion of IRD patients. In this study, we comprehensively analyzed the genetic spectrum of the USH2A gene, aiming to identify global hot spot mutations in USH2A-related IRDs and differences in hot spot regions across continents. Method: A retrospective USH2A-related IRD study was conducted, including our IRD cohort, and reported USH2A studies worldwide. Results: A total of 3972 mutated USH2A alleles of approximately 1935 patients were collected from 33 cohort studies worldwide, containing 102 alleles of 51 patients in our IRD cohort. Mutations in exon 13 were the most common, reaching 18.4% globally and a higher frequency of 22% in America, 19.2% in Europe, and a lower 12% in East Asia. Pathogenic mutations that affected 10 of the 72 exons of USH2A, exon2, exon 13, exon 41-43, exon 50, exon 54, exon 57, exon 61, and exon 63 in total were responsible for half of global USH2A mutant alleles. With base editors including adenine base editor (ABE), cytidine base editor (CBE), and glycosylase base editor (GBE), 76.3% of single nucleotide variations (SNVs) and 58% of all mutations in USH2A are correctable. Meantime, four novel pathogenic mutations were revealed in our IRD cohort, p. (Val1130Cysfs*72), p. (Ala2139fs*14), p. (Gly4139Arg) and p. (Val4166Cysfs*7). Conclusion: In this study, we revealed four novel mutations, expanding the spectrum of USH2A mutations, and importantly presented global hotspot exons and mutations of USH2A as well as the proportion of SNVs that can be restored by different base editors, providing a perspective for exploring high-efficiency and broader-reaching gene editing and gene therapies.